Cooperative Method of Request PLANNING IN IDENTITY Management systems - P. Yu. Piniuta; V. V. Bakhtizin (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki)
A number of planning methods was reviewed. The comparative analysis of the methods from the identity management adaptation point of view was produced. Cooperative method of request palning was created. Algorithm of best longterm request execuion time calulation was created for minimization blocked requests. It was based on history of requests to a target system. The results of experimental research were shown.